Carbon-containing bone hydroxyapatite obtained from tuna fish bone with high adsorption performance for Congo red. Issue 43 (22nd May 2017) - Peng, Qifan; Yu, Fan; Huang, Bicheng; Huang, Yaqin
Abstract : Carbon-containing nano-hydroxyapatite derived from fish bone was prepared as a high performance adsorbent for water treatment. Abstract : The carbon-containing bone hydroxyapatite (CBHA) has been obtained from tuna fish bone in which the carbon derived from the organics inside the bones acts as a dispersant. The XRD and TEM results indicated that the obtained HA is on the nanoscale and the N2 adsorption/desorption isotherm showed that CBHA has mesoporous structure with an enhanced specific surface area (1129.0 m 2 g −1 ). Moreover, CBHA as an adsorbent for removal of Congo red (CR) from aqueous solution exhibited high adsorption capacity (329.0 mg g −1 ) and the adsorption pattern fitted well with Langmuir model ( R 2 > 0.96). The adsorption kinetics of CBHA for CR followed the pseudo-second-order model. Thermodynamic parameters, including the Gibbs free energy (Δ G ), enthalpy (Δ H ), and entropy (Δ S ), indicated that the adsorption of CR onto CBHA was feasible, spontaneous, and endothermic at the temperature range of 303–323 K. Thus, CBHA as an efficient and low-cost adsorbent can be applied to the treatment of industrial effluents contaminated with CR.